NORMALIZATION OF AMERICAN-RUSSIAN RELATIONS DURING THE FIRST YEARS OF BARACK OBAMA`S PRESIDENCY - Пітей, Н. А. (PRECARPATHIAN BULLETIN OF THE SHEVCHENKO SCIENTIFIC SOCIETY Idea, 2019)
In this article, we investigated the alteration of foreign policy priorities by B. Obama’s administration comparing with his predecessor’s administration. We analyzed the state of bilateral relations between the United States of America (the US) and the Russian Federation at the beginning of B. Obama’s presidency. It was also explored the role of the US as a global player, whose activity in the foreign policy has a significant influence on processes in all continents. For Ukraine, the US foreign policy within the post-Soviet space has significant importance. After the collapse of the Union of Soviet Socialist Republics (USSR), the factors of American attention and commitment to Ukraine became the following ones: understanding that, with the end of the Cold War, situation in Europe was complicated according with some parameters, and Ukraine as a state located in the center of the continent is important; gradual growth of great-power tendencies in Russia’s political life; perceiving the relevance of Z. Brzezinski’s idea that after return of Ukraine to the Russian Federation, the last one obviously becomes an “empire”; an awareness of the interconnection between Ukraine’s sustainable development and security in Central and Eastern Europe, the interest in which among American authorities is traditional. Following the election of president B. Obama, the US declared refusal of confrontation policy, active interference in world processes in favor of cooperation and mutual understanding policy. The main reasons for changing the position of B. Obama`s administration towards Russia were the following ones: the mutual interest in cooperation on the new arms control treaty, common approaches to the war in Afghanistan and joint efforts to combat Iran`s nuclear ambitions. In the article, we proved that the analysis of the “reset” policy provides grounds for the following statement. It has became a temporary framework for the interaction between Russia and the US, aimed at improving the overall tone and solving tactical tasks which were important for both countries.